Beneficios del método Perfetti en el deterioro cognitivo en adultos mayores del Centro de Atención Integral de Rehabilitación Física, parroquia La Unión, Los Ríos, período octubre 2024 – abril 2025. - García Quishpi, José Armando (2025)
The main objective of this study is to determine the impact of the Perfetti Method in improving the cognitive functions of older adults who present mild or moderate cognitive impairment. Based on the activation of sensory, motor and cognitive processes, with the aim of stimulating brain plasticity and promoting the recovery of cognitive functions. A sample of older adults was selected from the Integral Care Center for Physical Rehabilitation, located in La Unión Parish, Los Ríos Province, Ecuador. The Perfetti Method is implemented on an individualized basis and then a periodic follow-up is performed to evaluate progress. Cognitive deterioration in older adults is a process given by the gradual decrease of essential abilities, such as memory, attention and language. These alterations can interfere with the daily life of the elderly and reduce their quality of life. The results of this study will provide scientific evidence on the efficacy of the Perfetti Method in the improvement of cognitive functions and the management of cognitive impairment.